The Role of Noncoding Genetic Variation in Isolated Orofacial Clefts. (October 2017) - Thieme, F.; Ludwig, K.U.
In the past decade, medical genetic research has generated multiple discoveries, many of which were obtained via genome-wide association studies (GWASs). A major GWAS finding is that the majority of risk variants for complex traits map to noncoding regions. This has resulted in a paradigm shift in terms of the interpretation of human genomic sequence variation, with more attention now being paid to what was previously termed "junk DNA." Translation of genetic findings into biologically meaningful results requires 1) large-scale and cell-specific efforts to annotate non-protein–coding regions and 2) the integration of comprehensive genomic data sets. However, this represents an enormous challenge, particularly in the case of human traits that arise during embryonic development, such as orofacial clefts (OFCs). OFC is a multifactorial trait and ranks among the most common of all human congenital malformations. These 2 attributes apply in particular to its isolated forms (nonsyndromic OFC [nsOFC]). Although genetic studies (including GWASs) have yielded novel insights into the genetic architecture of nsOFC, few data are available concerning causality and affected biological pathways. Reasons for this deficiency include the complex genetic architecture at risk loci and the limited availability of functional data sets from human tissues that represent relevant embryonic sites and time points. The present review summarizes current knowledge of the role of noncoding regions in nsOFC etiology. We describe the identification of genetic risk factors for nsOFC and several of the approaches used to identify causal variants at these loci. These strategies include the use of biological and genetic information from public databases, the assessment of the full spectrum of genetic variability within 1 locus, and comprehensive in vitro and in vivo experiments. This review also highlights the role of the emerging research field "functional genomics" and its increasing contribution to our biological understanding of nsOFC.